2018
DOI: 10.1002/14651858.cd013162
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for anxiety disorders in children and adolescents

Abstract: BackgroundPrevious Cochrane Reviews have shown that cognitive behavioural therapy (CBT) is e ective in treating childhood anxiety disorders. However, questions remain regarding the following: up-to-date evidence of the relative e icacy and acceptability of CBT compared to waiting lists/no treatment, treatment as usual, attention controls, and alternative treatments; benefits across a range of outcomes; longerterm e ects; outcomes for di erent delivery formats; and amongst children with autism spectrum disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
234
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(255 citation statements)
references
References 62 publications
11
234
3
7
Order By: Relevance
“…Clinical outcomes in the full sample were comparable to previously reported estimates [Hudson et al, , ; James et al, ]. Following treatment, 58% of the sample was free of their primary anxiety disorder diagnosis with this rate rising to 67% by follow‐up.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Clinical outcomes in the full sample were comparable to previously reported estimates [Hudson et al, , ; James et al, ]. Following treatment, 58% of the sample was free of their primary anxiety disorder diagnosis with this rate rising to 67% by follow‐up.…”
Section: Resultssupporting
confidence: 82%
“…Childhood anxiety disorders are very common [Kessler et al, ] and are associated with a wide range of impairments [Kim‐Cohen et al, ; Erath et al, ; Asendorpf et al, ]. Response to Cognitive Behavior Therapy (CBT) varies substantially between patients [James et al, ]. Identifying predictors of response is important given the potential for clinicians to identify children and adolescents at risk for poorer outcomes before treatment begins and to help inform the development of more efficacious therapies.…”
Section: Introductionmentioning
confidence: 99%
“…While this body of work suggests that CBT shows moderate effect sizes for co‐occurring anxiety and ASD in youth, there remains considerable heterogeneity in the effects between studies (Kreslins, Robertson, & Melville, ; Reynolds, Wilson, Austin, & Hooper, ; Ung, Selles, Small, & Storch, ), with estimates ranging from large (e.g., Chalfant et al, ) to small (e.g., Sofronoff, Attwood, & Hinton, ), and at least one documented instance of increased anxiety over treatment (as rated by parents, but not clinicians; Ooi et al, ). A Cochrane review further found that while CBT was effective for reducing anxiety diagnoses in youth with ASD when compared with waitlist controls, no differences were found when comparing CBT to active control treatments or treatment as usual (James, James, Cowdrey, Soler, & Choke, ), which aligns with other recent work showing no differences between CBT and person‐centered therapy for youth with co‐occurring ASD and anxiety (Murphy et al, ).…”
Section: Introductionsupporting
confidence: 70%
“…Furthermore, in spite of the empirical evidence of cognitive‐behavioral therapy effectiveness for children's anxiety problems (e.g., Cartwright‐Hatton, Roberts, Chitsabesan, Fothergill, & Harrington, ; James, James, Cowdrey, Soler & Choke., ), many parents do not seek professional help. Some predictors have been studied regarding parental recognition of their child's emotional or behavioral problems (e.g., their perception of the problem as nonsevere: Angold et al, ; Lyneham & Rapee, ) and help seeking (e.g., child's age, the amount of distress or burden parents experience in raising their child, and the existence of related medical or school problems: for a review, see Zwaanswijk, Verhaak, Bensing, van der Ende, & Verhulst, 2003).…”
Section: Introductionmentioning
confidence: 99%